2007
DOI: 10.2967/jnumed.107.039578
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Metabotropic Glutamate Receptor Subtype 5 Using PET and 11C-ABP688: Assessment of Methods

Abstract: 11 C-ABP688 is a new PET ligand to assess the subtype 5 metabotropic glutamate receptor (mGlu 5 ). The purpose of this study was to evaluate different methods for the analysis of human 11 C-ABP688 data acquired from 6 healthy, young volunteers. Methods: The methods were a 1-tissue-compartment model (K 1 , k 2 $), a 2-tissue-compartment model (K1-k4), and the noncompartmental method developed by Logan. Parameters related to receptor density were the total distribution volume (DV), DV$ (5 K 1 /k 2 $, 1 tissue co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 22 publications
7
55
0
Order By: Relevance
“…10,11 The regional time activity curves (TACs) were well fitted by the two-tissue compartment (2TC) model and Logan graphical approach. 11 However, a [ 11 C]ABP688 test-retest study in humans showed a significant increase in binding parameters in the second scan, which is currently unexplained. 12 [ 18 F]SP203 also displayed regional uptake consistent with the known distribution of mGluR5.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The regional time activity curves (TACs) were well fitted by the two-tissue compartment (2TC) model and Logan graphical approach. 11 However, a [ 11 C]ABP688 test-retest study in humans showed a significant increase in binding parameters in the second scan, which is currently unexplained. 12 [ 18 F]SP203 also displayed regional uptake consistent with the known distribution of mGluR5.…”
Section: Introductionmentioning
confidence: 99%
“…47 Figure 3). Moreover, age of onset of smoking correlated positively with mGluR5 availability in the frontal VOI (r=.41, p<.05) and thalamus (r=.45, p<.05), but this result also did not survive correction for age (p>.31).…”
Section: Drug Use Parameters and 11 C-abp688 Uptakementioning
confidence: 99%
“…Before the PET acquisition, a catheter was placed in the left antecubital vein for tracer injection and a low-dose CT was conducted for attenuation correction. In order to avoid inconvenient arterial blood sampling, we relied on a previously evaluated equilibrium paradigm 46,47 based on the premise that a steady-state between tracer concentration in tissue and blood can be obtained. 48 To verify that steady-state of receptor binding was reached after 45min (frames 17 to 19), timeactivity curves were generated for high (ACC, putamen), medium (thalamus), and low receptor density regions (cerebellum) in both hemispheres for all participants.…”
Section: Image Acquisition and Data Analysesmentioning
confidence: 99%
“…[18][19][20][21] [ 11 C]ABP688 shows fast kinetics and its binding can be reliably quantified using the NLS-SRTM as shown in previous PET studies in both animals [22][23][24] and humans, 25 where the results of NLS-SRTM showed a high correlation (r ⩾ 0.97) with those of a two-tissue compartment model despite small bias (see section Reference Region for [ 11 C]ABP688). Although its uptake pattern is consistent with mGluR5 distribution in the human brain, 19,26 a relatively moderate uptake in the brain due to lower affinity of [ 11 C]ABP688 to mGluR5 compared with others, 20,27,28 and the short half-life of [ 11 C] usually yield noisy dynamic PET data. Such noise properties of [ 11 C]ABP688, in addition to the wide distribution of the binding sites in the brain, should well allow differences to be seen at high noise levels among the parametric imaging approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In previous human studies using [ 11 C]ABP688 PET, 19,26,38 the ROI TACs for various brain regions including the cerebellum or its gray matter were best fitted by a two-tissue compartment model. The violation of the single-tissue compartment assumption for the reference region (and also tissue) would introduce biases to the gold standard.…”
Section: Reference Region For [ 11 C]abp688mentioning
confidence: 99%